2021
DOI: 10.1002/ps.6496
|View full text |Cite
|
Sign up to set email alerts
|

Adult damselflies as possible regulators of mosquito populations in urban areas

Abstract: BACKGROUND Dragonfly and damselfly larvae have been considered as possible biocontrol agents against young instars of mosquito vectors in urban environments. Yet our knowledge about adult odonate predation against mosquito adults is scarce. We quantified daily and annual predation rates, consumption rates and prey preferences of adult Hetaerina vulnerata male damselflies in an urban park. A focus on predation of mosquito species was provided, quantified their arbovirus (dengue, chikungunya and Zika) infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Notably, the control of pests and diseases in farmland by BI has been valued at over $400 billion annually worldwide (Costanza et al., 1997 ; Redhead et al., 2020 ). This also indirectly reduces the dosage application of pesticides, and further decreases environmental pollution (Cordoba‐Aguilar et al., 2021 ; Huang et al., 2020 ; Lyu et al., 2023 ). However, many reports indicated that the insects' abundance, especially the BI, was typically declining (Brooks et al., 2012 ; Ollerton et al., 2014 ; Powney et al., 2019 ), resulting in a decline of insect's service functions in the farmland (Oliver et al., 2015 ; Raven & Wagner, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the control of pests and diseases in farmland by BI has been valued at over $400 billion annually worldwide (Costanza et al., 1997 ; Redhead et al., 2020 ). This also indirectly reduces the dosage application of pesticides, and further decreases environmental pollution (Cordoba‐Aguilar et al., 2021 ; Huang et al., 2020 ; Lyu et al., 2023 ). However, many reports indicated that the insects' abundance, especially the BI, was typically declining (Brooks et al., 2012 ; Ollerton et al., 2014 ; Powney et al., 2019 ), resulting in a decline of insect's service functions in the farmland (Oliver et al., 2015 ; Raven & Wagner, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Schrama et al (2018), insect predator presence decreased mosquito larval survival and adult emergence by 20-50%. Many aquatic insects of the orders Coleoptera (DeSiervo et al 2020), Diptera (Moirangthem et al 2018), Hemiptera (Allo and Mekhlif 2019) and Odonata (Córdoba-Aguilar et al 2021) are known to be mosquito predators, commonly found with the mosquito immature in varied mosquito larval habitats including the wetland (Kumar 2009;Shaalan and Canyon 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the presence of other prey does not negatively affect the role of predators in controlling the population of mosquito larvae (Stav et al, 2005). Some aquatic bugs (Saha et al, 2007;Valbon et al, 2018Valbon et al, , 2019, larvivorous fishes (Das et al, 2018;Riaz et al, 2018), diving beetles (Choo et al, 2021;Lundkvist et al, 2003), and odonate nymphs (Córdoba-Aguilar et al, 2021;Cozzer et al, 2022;Samanmali et al, 2018) are among the natural predators that can help control the population of mosquito larvae. Odonate nymphs are voracious predators that use unique protractible labium to grab their prey, which includes mosquito larvae, various smaller aquatic invertebrates, and even larvae of fish and amphibians (Zia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They have drawn attention to their application in environmentally friendly mosquito control because of their predatory role against mosquito larvae (Subramanian, 2018). To the best of our knowledge, limited research works have been carried out regarding the efficacy of odonate nymphs in mosquito control in the world (Córdoba-Aguilar et al, 2021;Cozzer et al, 2022;Riaz et al, 2018). In Bangladesh, 102 species of odonates including 57 species of dragonflies and 45 species of damselflies have been recorded so far (Shah & Khan, 2020).…”
Section: Introductionmentioning
confidence: 99%